Hubungan antara keracunan timbal dengan anemia defisiensi besi pada anak - Bebi Trianita Sari; Bidasari Lubis (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Iron deficiency and lead poisoning often occurs simultaneously causing anemia and showed severe anemia. Conditions of iron deficiency anemia increases the incidence of lead poisoning due to lead and iron have the same receptors that Divalent Metal Transporter 1 (DMT 1). Prevention that children do not suffer from iron deficiency anemia is one way to prevent lead poisoning. In children with BLL above 45 mg / dL, first managed lead poisoning with chelation agents then overcome iron deficiency anemia.Keyword : iron deficiency, lead poisoning, anemia, children